Increasing Incidence of Zoonotic Visceral Leishmaniasis on Crete, Greece - Maria Antoniou; Ippokratis Messaritakis; Vasiliki Christodoulou; Ioanna Ascoksilaki; Nikos Kanavakis; Andrew J. Sutton; Connor Carson; Orin Courtenay (Emerging Infectious Diseases, 2009)
To determine whether the incidence of canine leishmaniasis has increased on Crete, Greece, we fitted infection models to serodiagnostic records of 8,848 dog samples for 1990–2006. Models predicted that seroprevalence has increased 2.4% (95% confidence interval 1.61%–3.51%) per year and that incidence has increased 2.2- to 3.8-fold over this 17-year period.